Alpha 2HS-glycoprotein in the serum and urine of patients with renal diseases. Issue 691 (May 1983) - Kishore, B. K.; Gejyo, F.; Arakawa, M.
Abstract : The concentration of alpha 2HS-glycoprotein (alpha 2HS-GP), as measured by the single radial immunodiffusion technique in the sera of 52 patients with various renal diseases and varying degrees of proteinuria, was found to be significantly reduced (P less than 0.001) when compared to the control values. Out of the 52 patients examined, 34 were found to excrete alpha 2HS-GP in urine with no correlation between the serum and urine levels of this protein. Although there is a statistically significant correlation between the clearances of albumin and alpha 2HS-GP, in only six patients were the clearances of alpha 2HS-GP within +/- 25% of albumin clearance. Twelve had higher, and 16 had lower, relative clearances of alpha 2HS-GP. The relative clearance of alpha 2HS-GP had no relation to the serum levels of alpha 2HS-GP, but correlated with the degree of proteinuria and the type of histological lesion in the kidney. In conclusion, there is a quantitative reduction of serum alpha 2HS-GP in patients with renal diseases. It appears that the degree of proteinuria and the type of renal lesion influences its selective handling by the kidneys.